Preparation method of flow battery graphite bipolar plate

By using fluoroplastic resin in graphite bipolar plates to form chemical crosslinking bonds with acidified graphite, and combining conductive polymers and coupling agents, the corrosion resistance and processing complexity of graphite bipolar plates in electrolytes are solved. The improvement of high conductivity and mechanical strength is achieved, simplifying the process and improving battery performance.

CN119116240APending Publication Date: 2024-12-13QINGDAO NANSHU TISING GRAPHITE PROD

Patent Information

Application Number
CN202411250155.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing graphite bipolar plates have poor corrosion resistance in electrolytes, which leads to oxidation of the resin layer, reduces conductivity and mechanical properties, and is complex in processing technology and is prone to cracking.

Method used

Fluoroplastic resin is used to form chemical crosslinking bonds with the acidified graphite particles, and combine conductive polymers and coupling agents to form a reinforced graphite bipolar plate structure through high-speed mixing and hot pressing to enhance mechanical strength and conductivity.

Benefits of technology

Improve the mechanical strength and conductivity of graphite bipolar plates, simplify the processing technology, reduce the influence of ohmic polarization, and is suitable for continuous production. The performance indicators reach tensile strength greater than 25MPa, bending strength greater than 30MPa, and surface conductivity ≥300S/ cm, battery energy efficiency is greater than 80%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a preparation method of a bipolar plate of a redox flow battery, which comprises the following steps: adding a coupling agent into resin and graphite powder, so that one end of the coupling agent is wound with the resin, the other end of the coupling agent is chemically crosslinked with the treated graphite powder to form a crosslinked net-shaped three-dimensional structure, and meanwhile, adding a conductive polymer to increase a conductive path between flexible graphite; the high-density graphite paper on the upper side and the lower side of the bipolar plate can prevent electrolyte of the flow battery from entering the bipolar plate, and the situation that the performance of the bipolar plate is reduced due to the fact that resin is in direct contact with the electrolyte is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of liquid flow batteries, and in particular relates to a method for preparing a graphite bipolar plate of a liquid flow battery. Background Art

[0002] Bipolar plates are important components of flow batteries and battery stacks, and they mainly play the roles of current collection, liquid separation, electron transmission, and heat dissipation. The main function of bipolar plates is current collection and conduction. Therefore, highly conductive materials are selected to construct multiple conductive pathways to reduce the overall internal resistance of bipolar plates and flow batteries, thereby improving the efficiency of flow batteries and reducing the impact of ohmic polarization on bipolar plates.

[0003] The bipolar plates currently available on the market are mainly pure graphite bipolar plates, carbon-plastic composite bipolar plates, and flexible graphite bipolar plates. Pure graphite bipolar plates have high mechanical strength, high electrical conductivity, and low internal resistance. However, thin graphite plates may crack during the installation of batteries or stacks due to uneven force, affecting the use of batteries or stacks. Pure graphite bipolar plates require high-pressure processing conditions and complex processes. Carbon composite bipolar plates are not as conductive as pure graphite bipolar plates. When the electrolyte is continuously flushed and in the presence of oxidizing ions and acidic conditions, conductive particles in the carbon composite bipolar plate will precipitate into the electrolyte, causing battery performance to deteriorate and test results to decrease. Flexible graphite bipolar plates are made by melt-bonding graphite sheets with epoxy resin, phenolic resin or other adhesive resins, and forming a stable conductive structure through cross-linking and curing between the resins. The resin can also be coated on the graphite surface, hot-pressed and cooled to shape. The main problem with this bipolar plate is that the synthetic resin is easily oxidized in the electrolyte, causing serious resin aging and stratification, resulting in unsatisfactory bipolar plate test results.

[0004] CN116640443 A discloses a liquid mixture for graphite bipolar plates, in which silver-plated nano copper powder and aniline pyrrole nano composites modified by the surface of silane coupling agent are added to the graphite epoxy system to greatly increase the conductivity of the graphite bipolar plate. However, the disadvantage is that if the electrolyte has strong acid and strong oxidizing properties, the epoxy resin and the metal powder in the bipolar plate will be oxidized and acidified, causing material aging, which will greatly reduce the mechanical properties and conductivity of the bipolar plate product.

[0005] In view of this, this application is hereby filed. Summary of the invention

[0006] The present invention provides a method for preparing a graphite bipolar plate for a liquid flow battery. The main reason for the corrosion resistance of the graphite bipolar plate is that the resin layer in the graphite bipolar plate is not resistant to the electrolyte and is oxidized. The method for preparing the graphite bipolar plate used in this patent can ensure the conductivity and mechanical strength of the bipolar plate.

[0007] The resins used in the present invention are all fluoroplastic resins. One end of the coupling agent is entangled with the resin and the conductive polymer, and the other end is chemically cross-linked with the acid-treated graphite particles to form a strong chemical cross-linking bond. The cross-linked resin molecules are transformed from long-chain structures to body structures, which greatly enhances the mechanical strength of the graphite bipolar plate. The graphite particles will form a certain interlayer structure under high temperature and high pressure, and the resin and the coupling agent will form a bridge between the layers to increase the mechanical strength of the product.

[0008] To achieve this purpose, the problem solved by the present invention adopts the following technical solution:

[0009] A method for preparing a graphite bipolar plate for a flow battery,

[0010] (1) Graphite powder impurity removal and oxidation treatment: expandable graphite powder is placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a certain proportion, hydrogen peroxide is added dropwise and stirred, and the mixture is subjected to slight heat treatment at 35-65°C for 2-6 hours. The acid-washed graphite powder is filtered, washed with deionized water until neutral, and dried in an oven at 70-100°C for 4-6 hours. The mixture is taken out and weighed for later use;

[0011] (2) mixing the graphite oxide powder in (1) with the diluted coupling agent, resin powder and conductive polymer in a high-speed mixer in a certain proportion, wherein the speed of the high-speed mixer is controlled at 500-1000 r / min and the mixing time is 10-30 min;

[0012] (3) Coating a small amount of a mixture of a release agent and a silane coupling agent on one side of a graphite paper and placing it on a mold, taking an appropriate amount of the powder in (2) and evenly spreading it on the graphite paper, controlling the thickness of the powder to be between 0.8 and 1.0 mm, and performing stamping after the temperature stabilizes;

[0013] (4) The temperature of the stamping equipment is controlled at 170-300°C, the pressure is controlled at 15-30MPa, the stamping time is 5-20min, the stamping frequency is 5-20 times / min, cooling and shaping, and opening the mold for sampling.

[0014] The bipolar plate components are calculated by mass percentage and include: 73-85% expandable graphite, 10-25% resin powder, 1-5% conductive polymer, the amount of coupling agent is 0.3%-1% of the total amount of resin graphite powder and conductive polymer; the amount of release agent is 10-25% of graphite paper, and the amount of coupling agent used for coating is 0.5-1% of graphite paper.

[0015] Preferably, the expandable graphite is acidified with concentrated nitric acid, concentrated sulfuric acid or a mixed acid, the mass ratio of the mixed acid is concentrated nitric acid: concentrated sulfuric acid = 1:1-1:2, the mass ratio of graphite to total acid is controlled between 1:3-1:4, the pickling time is 2-6 hours, the concentration of hydrogen peroxide is 30%, and the addition amount is 5%-15% of the graphite powder.

[0016] Preferably, the selected graphite powder is natural graphite, high-purity graphite, isostatic graphite, and the particle size of the graphite powder is between 50-500 mesh and the density is between 2-2.25g / cm 3 .

[0017] Preferably, the resin powder is one or more of PVDF, ETFE, and PFA, the tensile strength of the pure resin material is greater than 40 MPa, the resin particle size is between 50-500 mesh, and the particle size of the resin used is the same as the particle size of the graphite powder in the above three.

[0018] Preferably, the silane coupling agent includes any one or a combination of alkenyl silane coupling agent, epoxy silane coupling agent, amino silane coupling agent, monoalkoxy phosphate coupling agent and monoalkoxy pyrophosphate coupling agent.

[0019] The conductive polymer is one or more of polyacetylene, polyaniline, polypyrrole, polythiophene and poly(p-phenylene)ene.

[0020] Preferably, the release agent used includes one or more of methyl silicone oil, dimethyl silicone oil, dimethyl siloxane, silicone wax, and liquid paraffin.

[0021] Preferably, the bipolar plate manufacturing method and the amount of materials used are as follows, wherein the acid-treated graphite powder is mixed with a resin powder and a conductive polymer, wherein the graphite powder accounts for 73-85%, the resin powder accounts for 10-25%, and the conductive polymer alone accounts for 1-5%; the amount of silane coupling agent is 0.3%-1%; and the amount of release agent is 5-10% of the amount of graphite paper.

[0022] Preferably, the speed of the high-speed mixer is 500r / min-1000r / min; the temperature of hot pressing is 170℃-300℃, the pressure of hot pressing is 15-30MPa, and the stamping frequency is 5-20 times / min; when drying the oxidized graphite powder, the temperature of the blast oven is 70-100℃.

[0023] Preferably, the mold thickness is 0.8 mm, the thickness of the graphite paper used is 0.13 mm, and the density of the graphite paper is controlled at 1.65-1.8 g / cm 3 between.

[0024] Beneficial effects of the present invention

[0025] 1. The present invention solves the problem that the conductivity and mechanical properties of the existing graphite bipolar plates cannot be taken into account at the same time. The resin and coupling agent selected in the present invention can form a body structure with the oxidized graphite, and the bipolar plate can still maintain good mechanical strength when the amount of resin used is small; on the other hand, the conductive polymer selected in the present invention can form a new conductive path between the graphite layers, thereby increasing the conductivity of the material. The coupling agent and the release agent will be wrapped and filled in the tiny gaps on the surface of the graphite paper, which will prevent the electrolyte from entering the interior of the bipolar plate, causing the electrolyte to directly contact with the resin and the graphite powder, thereby reducing the battery performance.

[0026] 2. The present invention adopts a one-time heating and stamping method, which avoids the processing difficulties of the bipolar plate due to high-pressure forming, grinding, etc., simplifies the preparation process and flow of the bipolar plate, and the raw materials used are widely available and suitable for continuous production;

[0027] 3. The powder resin used in the present invention has a density of 1.77-2.0 g / cm 3 The density of graphite powder after oxidation treatment is between 1.8-2.0g / cm 3 , and the particle sizes of the two are kept consistent, which can ensure that the resin powder is evenly attached to the graphite powder and ensure that the thickness of the bipolar plate after stamping is uniform and stable.

[0028] 4. The bipolar plate made by the above method has the following technical indicators: the tensile strength of the bipolar plate is greater than 25MPa, the bending strength is greater than 30MPa, the surface conductivity of the bipolar plate is ≥300S / cm, and the surface resistance is <20mΩ.cm 2 , tested in an all-vanadium flow battery: 200mA / cm 2 After 100 cycles, the battery's energy efficiency is greater than 80%, the coulombic efficiency is greater than 98%, and the capacity retention rate is greater than 80%. DETAILED DESCRIPTION

[0029] In order to illustrate the technical features and product performance of the present invention, the present invention is described in detail in conjunction with the following embodiments, but the protection scope of the present invention is not limited thereto.

[0030] Embodiment 1

[0031] In this embodiment, the following formula is used: 42.4g of expandable natural graphite powder (particle size is 100 mesh), the mass ratio of concentrated sulfuric acid and concentrated nitric acid in the acidification treatment is 2:1, the amount of concentrated sulfuric acid added is 84.8g, the mass of concentrated nitric acid added is 42.4g, the mass ratio of concentrated sulfuric acid and concentrated nitric acid to graphite powder and natural graphite powder is 3:1, the mass of hydrogen peroxide added is 6.36g (15% of the mass of graphite powder), and the acidified graphite oxide 42.5g (mass fraction is 8 5%), 5g (mass fraction of 10%, particle size of 100 mesh) of PVDF resin added, 2.35g (mass fraction of 4.7%) of conductive polymer polyaniline, 0.15g (mass fraction of 0.3%) of coupling agent KH-550, 1.62g (10% of the total mass of graphite paper) of release agent, 0.18g (ratio of release agent to coupling agent is 9:1) of coupling agent on graphite paper, and the total mass of graphite paper is 16.2g.

[0032] The reason why graphite is conductive is that there are a large number of coplanar layers in its crystal structure and a continuous π-bond covalent bond network in its electronic band structure, which makes graphite have good conductivity. In this embodiment, the proportion of graphite reaches 85%, the contact opportunities between the graphite layers are increased, and the conductive paths are increased. If the resin content is less than 10%, the system composed of resin and graphite mainly reflects the brittleness of graphite, and the mechanical strength will be greatly reduced.

[0033] In Example 1, low resin content and coupling agent dosage are used, and the mechanical strength of the produced bipolar plate can meet the use requirements.

[0034] Process requirements: In this embodiment, natural graphite powder is first treated with concentrated sulfuric acid and concentrated nitric acid, and then a small amount of hydrogen peroxide is added, which can not only remove some impurities remaining in the graphite powder, but also oxidize the graphite powder into functional groups such as -OH, -COOH, -NH2, epoxy, etc., coupling agent {taking KH-550 as an example, NH2CH2CH2CH2Si(OC2H5)3}, the amino group of the coupling agent forms an amide bond with the carboxyl group in the graphite oxide, and OC2H5 and the long chain of the resin are intertwined, forming a physical and chemical crosslinking between the resin and the graphite, which increases the mechanical strength of the bipolar plate. The reason for choosing the reaction at 60°C is that the reaction rate at this temperature is moderate. High temperature will cause the system composed of concentrated acid and hydrogen peroxide to react violently, resulting in uneven density of the graphite powder. If the temperature is too low, the reaction activity is low, and the oxidized groups are less, which is not conducive to the chemical crosslinking of the coupling agent and affects the mechanical properties. Therefore, 60°C will make the surface treatment of the graphite powder more complete and the structure will not be destroyed. 2. The oxidized graphite powder, conductive polymer, resin and diluted coupling agent are mixed in a high-speed mixer at a speed of 800r / min. The main purpose is to make the coupling agent evenly dispersed on the surface of the graphite powder, and the resin and conductive polymer can be evenly mixed with the graphite powder to ensure that the cross-linked structure formed by the heated stamping coupling agent and the surface groups of the graphite powder and the resin is evenly present in the system. 3. The purpose of preheating the graphite paper-powder-graphite paper structure in step 3 is to soften the powder and prevent the powder from penetrating the graphite paper due to the pressure of the stamping, causing damage to the graphite paper and affecting the battery test results. The temperature of the stamping machine is controlled at 170°C because the melting point of the PVDF resin used is 160°C, so 270°C is used for stamping. The stamping frequency is 10 times / min, which can ensure the integrity of the bipolar plate product. A method for preparing graphite bipolar plates for all-vanadium liquid flow batteries, the specific process is as follows:

[0035] 1. Acidification and oxidation treatment of expandable graphite powder: 42.40g natural graphite powder (particle size of 100 mesh) was added to a solution prepared by 84.8g of concentrated sulfuric acid and 42.4g of concentrated nitric acid, and heated to 60°C. After stirring for 30min, 6.36g of 30% hydrogen peroxide was added dropwise, and the mixture was continued to be stirred for 1h before filtering. After being washed with deionized water, the mixture was dried in an oven at 70-100°C, and 42.5g of graphite powder was obtained by weighing.

[0036] 2. Weigh 0.15g of silane coupling agent (KH-550) and dissolve it in 10ml of ethanol solution, weigh 2.35g of conductive polymer polyaniline, 5g of PVDF resin (particle size is 100 mesh), and the graphite powder obtained after acidification and oxidation treatment in 1, and place them in a high-speed mixer for high-speed mixing and stirring at a speed of 800r / min, and take them out after stirring for 20min;

[0037] 3. Weigh 1.62g of dimethyl silicone oil and 0.18g of silane coupling agent (KH-550), mix them, and evenly apply them on one side of two graphite papers with a total mass of 16.2g and a thickness of 0.13mm, and take an appropriate amount of the mixed powder obtained in 2. Evenly spread 0.8mm of the mixed powder in 2 between two graphite papers not coated with silicone oil and coupling agent, put it on a mold with a thickness of 0.8mm, and preheat it on a punching machine;

[0038] 4. When the temperature of the punching machine is stable at 170°C, after 20 minutes, set the frequency of the punching machine to 10 times / min and the pressure of 15MPa for punching. After cooling, a bipolar plate with a thickness of 0.8mm is made;

[0039] 5.Performance test according to NB / T42007-2013 "Mechanical Performance Test Method of All-vanadium Redox Flow Battery Bipolar Plate" and the battery test method of all-vanadium redox flow battery industry standard;

[0040] Embodiment 2

[0041] In this embodiment, the following formula is used: 72.8g natural graphite powder, 194.1g concentrated sulfuric acid, 97.1g concentrated nitric acid, the mass ratio of concentrated sulfuric acid and concentrated nitric acid to high-purity graphite powder is 4:1, and the mass ratio of concentrated sulfuric acid to concentrated nitric acid is 2:1. 73g (mass fraction of 73%) of oxidized high-purity graphite is obtained, 25g (mass fraction of 25%, particle size of 200 mesh), 1g (mass fraction of 1%) of coupling agent conductive polymer, 1g (mass fraction of 1%) of coupling agent, 3.22g (accounting for 20% of the total mass of graphite paper) of release agent, 0.36g (the ratio of release agent to coupling agent is 9:1) of coupling agent on graphite paper, and the total mass of graphite paper is 16.1g.

[0042] In this embodiment, a high resin content (mass fraction of 25%) is used to achieve high strength of the bipolar plate while having excellent electrical properties. In this embodiment, a high coupling agent content is used, and the coupling mechanism is the same as in Example 1, and the tensile and bending strength of the bipolar plate is increased by increasing the number of cross-linked network structures formed between the coupling agent, the resin, and the graphite oxide.

[0043] Process requirements: 1. Excessive concentrated sulfuric acid and concentrated nitric acid are used to ensure that graphite can be fully oxidized and produce sufficient oxidized groups (-OH, -COOH, -NH2, etc.) 2. The particle size of natural graphite powder and resin powder is consistent, and powders of the same mesh size can be better mixed; 3. The amount of coupling agent added is 1% (the normal amount is 3‰-8‰), and sufficient coupling agent is used to ensure sufficient cross-linking structure (cross-linking system between resin, coupling agent, and graphite oxide); 4. Preheating at 170℃ is used to ensure that the resin has been softened before stamping to prevent graphite powder resin and conductive polymer from piercing graphite paper and affecting the battery performance test of bipolar plates. The stamping pressure is selected as 15MPa.

[0044] A method for preparing a graphite bipolar plate for an all-vanadium liquid flow battery, the specific process is as follows:

[0045] 1. Acidification and oxidation treatment of expandable graphite powder: 72.8g natural graphite powder (particle size 200 mesh) was added to a solution prepared by 194.1g concentrated sulfuric acid and 97.1g concentrated nitric acid, and heated to 60°C. After stirring for 30min, 7.3g of 30% hydrogen peroxide was added dropwise, and the mixture was stirred for 3.5h and filtered. After being washed with deionized water, the mixture was dried in an oven at 70-100°C, and 73g of graphite powder was obtained by weighing.

[0046] 2. Weigh 1g of silane coupling agent (KH-550) and dissolve it in 20ml of ethanol solution. Then weigh 1g of conductive polymer polyaniline, 25g of PVDF (particle size 200 mesh) resin, and the graphite powder obtained after acidification and oxidation treatment in 1, and place them in a high-speed mixer for high-speed mixing and stirring at a speed of 800r / min. Stir for 20min and then take them out;

[0047] 3. Weigh 3.22g of dimethyl silicone oil and 0.16g of silane coupling agent (KH-550) and mix them. Apply them on one side of two graphite papers with a total mass of 16.1g and a thickness of 0.13mm, and take an appropriate amount of the mixed powder obtained in 2. Evenly spread 0.8mm of the mixed powder in 2 between two graphite papers not coated with silicone oil and coupling agent, and put them on a punching machine for preheating;

[0048] 4. When the temperature of the punching machine is stable at 170°C, after 20 minutes, set the frequency of the punching machine to 10 times / min and the pressure of 15MPa for punching. After cooling, a bipolar plate with a thickness of 0.8mm is made;

[0049] 5.Performance test according to NB / T42007-2013 "Mechanical Performance Test Method of All-vanadium Redox Flow Battery Bipolar Plate" and the battery test method of all-vanadium redox flow battery industry standard;

[0050] Embodiment 3

[0051] The following formula is used in this embodiment: 39.3g natural graphite powder, 91.9g concentrated sulfuric acid, 45.9g concentrated nitric acid, the mass ratio of concentrated sulfuric acid to concentrated nitric acid is close to 2:1, 1.96g hydrogen peroxide (the addition amount is 5% of the graphite powder), and 39.4g of graphite oxide powder (mass fraction is 78.8%) is obtained, 8g PVDF resin (mass fraction is 16%) is added, 2.5g conductive polymer (mass fraction is 5%), 0.26g coupling agent KH-550 (mass fraction is 5.2%), 16.2g graphite paper mass, 2.43g release agent (accounting for 15% of the mass of graphite paper), and 0.27g silane coupling agent (mass ratio of release agent to coupling agent is 9:1).

[0052] This embodiment mainly takes into account the conductivity and mechanical strength of the bipolar plate. Compared with Example 2, the amount of conductive polymer is increased, the amount of graphite powder is increased, the contact probability between graphites is increased, the conductivity inside the bipolar plate is increased, and the amount of resin is reduced, so that the network structure formed by the coupling agent and the resin is reduced, and the mechanical properties of the material are slightly reduced.

[0053] A method for preparing a graphite bipolar plate for an all-vanadium liquid flow battery, the specific process is as follows:

[0054] 1. Acidification and oxidation treatment of expandable graphite powder: 39.30g natural graphite powder (150 mesh) was added to a solution prepared by 91.9g concentrated sulfuric acid and 45.9g concentrated nitric acid, and heated to 60°C. After stirring for 30min, 1.96g of 30% hydrogen peroxide was added dropwise, and the mixture was stirred for 4h before filtering. After washing with deionized water, the mixture was dried in an oven at 70-100°C, and 39.4g of graphite oxide powder was obtained by weighing.

[0055] 2. Weigh 0.25g of silane coupling agent (KH-550) and dissolve it in 10ml of ethanol solution. Then weigh 2.5g of conductive polymer poly(p-phenylene vinylene), 8g of PVDF (150 mesh) resin, and the graphite powder obtained after acidification and oxidation treatment in 1. Place them in a high-speed mixer for high-speed mixing and stirring at a speed of 800r / min. Stir for 20min and then take them out;

[0056] 3. Weigh 2.43g of dimethyl silicone oil and 0.27g of silane coupling agent (KH-550) and mix them. Apply them on one side of two graphite papers with a size of 200mm*200mm, a mass of 16.2g and a thickness of 0.13mm. Take an appropriate amount of the mixed powder obtained in 2 and evenly spread 0.8mm of the mixed powder in 2 between two graphite papers that are not coated with silicone oil and coupling agent. Put it on a mold with a thickness of 0.8mm and preheat it on a punching machine;

[0057] 4. When the temperature of the punching machine is stable at 170°C for 20 minutes, set the punching machine frequency to 10 times / min and the pressure to 15MPa for punching. After cooling, a bipolar plate with a thickness of 0.8mm is made;

[0058] 5.Performance test is carried out according to NB / T42007-2013 "Mechanical Performance Test Method of All-vanadium Liquid Flow Battery Bipolar Plate" and the battery test method of all-vanadium liquid flow battery industry standard.

[0059] The bipolar plates in the above embodiments were cut into corresponding test specimens according to NB / T42007-2013 for mechanical property testing; according to the test standards specified in the flow battery industry, the above bipolar plate products were made into rectangular samples of 110mm*70mm and punched, and the Nafion212 membrane produced by DuPont was used for battery testing, and compared with commercially available bipolar plate products. The results are shown in Table 1 below:

[0060]

[0061] Compared with commercially available bipolar plates, the bipolar plate of the present invention has better mechanical properties and battery test performance than commercially available bipolar plate products. The present invention adopts hot pressing and stamping to ensure the internal compactness of the bipolar plate, and the close contact between the graphite layers. The high-strength resin used is evenly filled between the graphites, ensuring the uniformity and stability of the internal structure of the bipolar plate. The electrical conductivity far exceeds that of other similar products. This process can greatly improve the electrical conductivity and mechanical strength of the product.

[0062] According to the description and embodiments of the present invention, relevant technical personnel can change and modify the above-mentioned implementation methods. The technical scope of the present invention is not limited to the above-mentioned description. Modifications and changes to the present invention also belong to the scope of the present invention. The technical scope must be determined based on the scope of the claims.

Claims

1. A method for preparing a graphite bipolar plate for a flow battery, characterized in that: (1) Graphite powder impurity removal and oxidation treatment: expandable graphite powder is placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a certain proportion, hydrogen peroxide is added dropwise and stirred, and the mixture is subjected to slight heat treatment at 35-65°C for 2-6 hours. The acid-washed graphite powder is filtered, washed with deionized water until neutral, and dried in an oven at 70-100°C for 4-6 hours. The mixture is taken out and weighed for later use; (2) mixing the graphite oxide powder in (1) with the diluted coupling agent, resin powder and conductive polymer in a high-speed mixer in a certain proportion, wherein the speed of the high-speed mixer is controlled at 500-1000 r / min and the mixing time is 10-30 min; (3) Coating a small amount of a mixture of a release agent and a silane coupling agent on one side of a graphite paper and placing it on a mold, taking an appropriate amount of the powder in (2) and evenly spreading it on the graphite paper, controlling the thickness of the powder to be between 0.8 and 1.0 mm, and performing stamping after the temperature stabilizes; (4) The temperature of the stamping equipment is controlled at 170-300°C, the pressure is controlled at 15-30MPa, the stamping time is 5-20min, the stamping frequency is 5-20 times / min, cooling and shaping, and opening the mold for sampling. The bipolar plate components are calculated by mass percentage and include: 73-85% expandable graphite, 10-25% resin powder, 1-5% conductive polymer, the amount of coupling agent is 0.3%-1% of the total amount of resin graphite powder and conductive polymer; the amount of release agent is 10-25% of graphite paper, and the amount of coupling agent used for coating is 0.5-1% of graphite paper.

2. The method for preparing a graphite bipolar plate for a flow battery according to claim 1, characterized in that: The expandable graphite is acidified by using concentrated nitric acid, concentrated sulfuric acid or a mixed acid. The mass ratio of the mixed acid is concentrated nitric acid: concentrated sulfuric acid = 1:1-1:

2. The mass ratio of graphite to total acid is controlled between 1:3-1:

4. The pickling time is 2-6 hours. The concentration of hydrogen peroxide is 30%, and the drop amount is 5%-15% of the graphite powder.

3. The method for preparing a graphite bipolar plate for a flow battery according to claim 1 or 2, characterized in that: The selected graphite powder is natural graphite, high purity graphite, isostatic graphite, the particle size of graphite powder is between 50-500 mesh, and the density is between 2-2.25g / cm 3 .

4. The method for preparing a graphite bipolar plate for a flow battery according to claim 1, characterized in that: The resin powder is one or more of PVDF, ETFE and PFA. The tensile strength of the pure resin material is greater than 40MPa. The resin particle size is between 50-500 meshes. The particle size of the resin used is the same as that of the graphite powder in the above three examples.

5. The method for preparing a graphite bipolar plate for a flow battery according to claim 1, characterized in that: The silane coupling agent includes any one or a combination of alkenyl silane coupling agents, epoxy silane coupling agents, amino silane coupling agents, monoalkoxy phosphate coupling agents and monoalkoxy pyrophosphate coupling agents.

6. The method for preparing a graphite bipolar plate for a flow battery according to claim 1, characterized in that: The conductive polymer is one or more of polyacetylene, polyaniline, polypyrrole, polythiophene and poly(p-phenylene)ene.

7. The method for preparing a graphite bipolar plate for a flow battery according to claim 1, characterized in that: The release agent used includes one or more of methyl silicone oil, dimethyl silicone oil, dimethyl siloxane, silicone wax, and liquid paraffin.

8. The method for preparing a graphite bipolar plate for a flow battery according to claim 1, characterized in that: The bipolar plate manufacturing method and material dosage are as follows, wherein the acid-treated graphite powder is mixed with resin powder and conductive polymer, wherein the graphite powder accounts for 73-85%, the resin powder accounts for 10-25%, and the conductive polymer accounts for 1-5%; the silane coupling agent dosage is 0.3%-1%; and the release agent dosage is 5-10% of the graphite paper dosage.

9. The method for preparing a graphite bipolar plate for a flow battery according to claim 1, characterized in that: The speed of the high-speed mixer is 500r / min-1000r / min; the temperature of hot pressing is 170℃-300℃, the pressure of hot pressing is 15-30MPa, and the stamping frequency is 5-20 times / min; when drying the oxidized graphite powder, the temperature of the blast oven is 70-100℃.

10. The method for preparing a graphite bipolar plate for a flow battery according to claim 1, wherein the mold thickness is 0.8 mm, the thickness of the graphite paper used is 0.13 mm, and the density of the graphite paper is controlled at 1.65-1.8 g / cm 3 between.

Citation Information

Patent Citations

  • Liquid resin composition for preparing graphite bipolar plate as well as preparation method and application of liquid resin composition

    CN116640443A

Cited By

  • Fast charging graphite, preparation method thereof and lithium ion battery negative electrode material

    CN120987315A

  • A fast-charging graphite, a preparation method thereof and a lithium ion battery negative electrode material

    CN120987315B

  • High-conductivity carbon fiber material, preparation method thereof and application of high-conductivity carbon fiber material in bipolar plate of flow battery

    CN121023808A

  • Bipolar plate of all-vanadium redox flow battery and preparation method of bipolar plate

    CN122025687A

  • Preparation method of composite bipolar plate for proton exchange membrane iron-chromium flow battery and hydrogen preparation regulation

    CN122117949A